Inside the Micro-politics of Repression. Institutional Control and Political Neutralization of Non-Profit Organizations in a French City - Chevallier, Thomas; Talpin, Julien (PARTECIPAZIONE E CONFLITTO, 2026)
This article shows how understanding repressive phenomena in liberal democracies requires conceptualizing them within the framework of a deeper and more diffuse dynamic of institutional control and political neutralization of civil society organizations through funding and partnerships. To do so, we examine, through a research conducted in Lille, a municipality in northern France, what we propose to call a micro-politics of repression. We focus more specifically on the micro-political processes of control and repression in this city through two case studies that show how partnership relationships can, depending on events and conflicts linked to the asymmetrical nature of these relationships, tip the balance towards certain forms of more or less overt reprimand and repression. In conclusion, we open the discussion on the importance of a joint understanding of the phenomena of institutional control, political neutralization, and repression with a broader reflection on the restriction of civic space in Western democracies.